2023
DOI: 10.3390/jof9020268
|View full text |Cite
|
Sign up to set email alerts
|

Vacuole Proteins with Optimized Microtubule Assembly Is Required for Fum1 Protein Localization and Fumonisin Biosynthesis in Mycotoxigenic Fungus Fusarium verticillioides

Abstract: Fumonisin contamination of corn caused by Fusarium verticillioides is a major concern worldwide. While key genes involved in fumonisin biosynthesis are known, the location within the fungal cell where this process occurs has yet to be fully characterized. In this study, three key enzymes, i.e., Fum1, Fum8, and Fum6, associated with early steps of fumonisin biosynthesis pathway, were tagged with GFP, and we examined their cellular localization. Results showed that these three proteins co-localized with the vacu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Our recent study demonstrated the crucial role of vacuoles as an important intracellular organelle in FB 1 biosynthesis [39]. We hypothesized that deletion of Med1 may alter vacuolar morphology, thereby leading to enhanced FB 1 biosynthesis.…”
Section: Med1 Lxxll Mutations Significantly Stimulate Fb 1 Biosynthes...mentioning
confidence: 98%
See 1 more Smart Citation
“…Our recent study demonstrated the crucial role of vacuoles as an important intracellular organelle in FB 1 biosynthesis [39]. We hypothesized that deletion of Med1 may alter vacuolar morphology, thereby leading to enhanced FB 1 biosynthesis.…”
Section: Med1 Lxxll Mutations Significantly Stimulate Fb 1 Biosynthes...mentioning
confidence: 98%
“…organelle in FB1 biosynthesis [39]. We hypothesized that deletion of Med1 may alter vacuolar morphology, thereby leading to enhanced FB1 biosynthesis.…”
Section: Med1 Lxxll Mutations Significantly Stimulate Fb 1 Biosynthes...mentioning
confidence: 99%
“…An efficient and stable genetic transformation system has been developed, including Agrobacterium -mediated transformation (ATMT) and PEG-mediated protoplast transformation . These systems enable the introduction of desired genetic modifications into the fungal genome, including gene knockouts and gene replacements . However, the generation of mutants in F.…”
Section: Introductionmentioning
confidence: 99%